Pituitary dysfunction following cranial radiotherapy for adult‐onset nonpituitary brain tumours. (24th November 2015) - Kyriakakis, Nikolaos; Lynch, Julie; Orme, Steve M.; Gerrard, Georgina; Hatfield, Paul; Loughrey, Carmel; Short, Susan C.; Murray, Robert D.
Summary: Objective: There are limited data concerning the evolution of radiation‐induced hypopituitarism in adult‐onset brain tumour (AO‐BT) survivors, in part the consequence of the limited survival of many of these individuals. We aim to characterize the pituitary‐related outcomes following cranial radiotherapy (cXRT) for adult‐onset primary nonpituitary brain tumours. Design: We retrospectively analysed longitudinal data of patients with AO‐BT who received cXRT within a tertiary cancer referral centre. Patients: A total of 107 adults (age 40·0 ± 13·1 years) followed for a median duration of 8 years following cXRT. Measurements: Prevalence of radiotherapy‐induced hypopituitarism. Results: 94·4% received fractionated photon radiotherapy (median dose 54 Gy), while the remaining patients received proton beam or stereotactic radiotherapy. 88·8% of patients developed hypopituitarism during follow‐up. The frequency of GH, gonadotrophin, ACTH and TSH deficiencies was 86·9% (severe GHD 64·5%, partial GHD 22·4%), 34·6%, 23·4% and 11·2%, respectively. ACTH deficiency was clinically significant, necessitating glucocorticoid replacement, in only 10·3% of cases. Hyperprolactinaemia developed in 15% of patients, which was persistent in only 50% of cases. Multiple pituitary hormone deficiencies were present in 47·7% of patients, encountered more frequently in patients with tumours in proximity to the sella. Longitudinal data analysis revealed accumulation of hormone deficits throughout the follow‐up period, with incidence of all pituitary hormone deficiencies almost doubling between years 2 and 7 of follow‐up. Conclusions: Pituitary dysfunction in AO‐BT survivors following cXRT is a common, evolving, time‐dependent phenomenon. It is important that deficits are identified early and replacement therapies introduced to optimize quality of life in these individuals, where prognosis is often guarded.